ANALISIS SELF ASSESSMENT SYSTEM DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK HOTEL DI KABUPATEN KARIMUN, PROVINSI KEPULAUAN RIAU - Septiana Dwiputrianti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2013)
Tax is one of the main state revenues that is important for governmental operation and developments. Hotel tax in Karimun Regency had implemented self-assessment system, which tax payers calculate their own tax payment, andreport. The purpose of this article is to analyse the implementation of self-assessment system in enhancing the compliance of hotel tax payers in Karimun Regency. Moreover, the study also assessing factors influencing the willingness of tax payers to pay tax. A qualitative-descriptive research method employed with collection data from participatory observation, interviews, and documents.This study found that the implementation of self-assessment system of hotel tax has not yet been applied properly. It could be seen from tax payers who didn't understand on the regional government regulation on self-assessment system.This is due to the lack of information from the government. Moreover, it found that tax payers also intentionally ignored to pay the tax, had low honesty and discipline in filling the form of self assessment.